Dance, disability, accessible education and teacher training: experiences and theorizations in process (Revista Educação, Artes e Inclusão, 2020)
This text presents the experiences and reflections of a teacher working in disciplines dedicated to inclusive perspectives on theory and practice in undergraduate dance courses. Over the course of two decades, the author's perceptions of changes in the political-educational scenario within educational and artistic contexts are the motivation for constant reflection on concepts, themes for study, methodologies and proposals to be developed with students who are destined to become teachers. These experiences bring to light the ethical, political, aesthetic, poetic, artistic and pedagogical foundations that guide the composition of the curriculum, the potential of practice as a curricular component that orientates the teaching-learning processes, the importance of collaborations between the academic space and other social segments and, the classroom as a space for compositions and encounters in diversity. It is concluded that despite significant advances, studies on dance, disability and accessible education, are still necessary, underlining the relevance of space-times of experiences and critical reflection in dance teacher training courses.